Peran Konsultan Pajak dalam Meningkatkan Kepatuhan Wajib Pajak atas Kenaikan Tarif PPN : Atribusi Perilaku - Adinda Tri Ameliasari; Ulfa Puspa Wanti Widodo (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This study aims to comprehensively analyze the role of tax consultants in improving taxpayer compliance with the Value Added Tax (VAT) rate increase policy from 11% to 12%, which will take effect in 2025. The research adopts attribution theory to explore how professional assistance can influence taxpayers’ perception and behavioral shifts toward compliance. A descriptive qualitative method was employed, with data collected through literature studies, participatory observation, and semi-structured interviews involving one tax consultant and two taxpayers who received VAT reporting assistance. The findings reveal that the role of tax consultants extends beyond administrative functions. They not only assist in technical adjustments such as Coretax system configuration and Periodic VAT Return reporting but also play a crucial role in fostering fiscal awareness through educational and psychological approaches. Empirically, consultant assistance improved clients’ reporting timeliness from 68% to 91% and reduced tax invoice errors by 27% within a three-month mentoring period. Moreover, consultants contributed to shifting taxpayers’ attribution from external factors—such as blaming the system or regulations—to internal factors, including personal awareness and responsibility. These results demonstrate that the presence of tax consultants strengthens both formal and material compliance, leading to sustainable, awareness-based tax behavior. Therefore, tax consultants serve as catalysts for behavioral transformation and play a strategic role in shaping an adaptive fiscal culture amid dynamic taxation policy changes in Indonesia.